Sedation in Gastrointestinal Endoscopy - Benvenuto Axel; Marcellus Simadibrata (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2018)
Sedation helps patients to tolerate uncomfortable gastrointestinal endoscopy procedures by relieving anxiety and pain. It also decreases a patient’s risk of physical injury during gastrointestinal endoscopy procedures while providing the endoscopist with a good environment for an optimum examination. Not all sedation in gastrointestinal endoscopy is managed by an anesthesiologist. Using sedation has increases risk of cardiopulmonary complications. Therefore, sedation is an important part in gastrointestinal endoscopy to learn. This review will focus on basic pharmacology of sedatives and analgesic, common used drugs in sedation (Propofol, Midazolam, Fentanyl), and their use in gastrointestinal endoscopy.